A Microbial‐Mineralization Approach for Syntheses of Iron Oxides with a High Specific Surface Area. Issue 14 (28th February 2013) - Yagita, Naoki; Oaki, Yuya; Imai, Hiroaki
<x xml:space="preserve">Abstract</x> Of minerals and microbes: A microbial‐mineralization‐inspired approach was used to facilitate the syntheses of iron oxides with a high specific surface area, such as 253 m2 g−1 for maghemite (γ‐Fe2O3) and 148 m2 g−1 for hematite (α‐Fe2O3). These iron oxides can be applied to electrode material of lithium‐ion batteries, adsorbents, and catalysts.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>